2005
DOI: 10.1091/mbc.e05-01-0073
|View full text |Cite
|
Sign up to set email alerts
|

Induction of theCandida albicansFilamentous Growth Program by Relief of Transcriptional Repression: A Genome-wide Analysis

Abstract: Candida albicans, the major human fungal pathogen, undergoes a reversible morphological transition from blastospores (round budding cells) to filaments (elongated cells attached end-to-end). This transition, which is induced upon exposure of C. albicans cells to a number of host conditions, including serum and body temperature (37°C), is required for virulence. Using whole-genome DNA microarray analysis, we describe 61 genes that are significantly induced (>2-fold) during the blastospore to filament transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
306
5
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(339 citation statements)
references
References 58 publications
22
306
5
6
Order By: Relevance
“…4E) and mediated by a complex transcriptional network (8,24). In addition to nutrient-poor Spider media, mammalian serum also induces hyphae (25,26), and we observed that filastatin inhibited the response to both these stimuli (Fig. 3B).…”
Section: Filastatin Inhibits Hyphal Morphogenesis and Colony Morphologymentioning
confidence: 62%
“…4E) and mediated by a complex transcriptional network (8,24). In addition to nutrient-poor Spider media, mammalian serum also induces hyphae (25,26), and we observed that filastatin inhibited the response to both these stimuli (Fig. 3B).…”
Section: Filastatin Inhibits Hyphal Morphogenesis and Colony Morphologymentioning
confidence: 62%
“…Flo8 is a potential cofactor of Efg1 at the promoters of hypha-specific genes as the two regulators interact with each other and share a common set of target genes . Negative regulators of the hyphal-specific transcription, such as Nrg1 and Sfl1 (Braun et al, 2001;Murad et al, 2001;Garcia-Sanchez et al, 2005;Kadosh and Johnson, 2005;Bauer and Wendland, 2007;Li et al, 2007), are also potential candidates that can function to repress the transcription during yeast growth by keeping H4 acetylation levels low. Future experiments need to address the identity and mechanisms of how these regulators are induced in response to extracellular stimuli and regulate hypha-specific nucleosomal H4 acetylation.…”
Section: Efg1 Interacts With Nua4 In Vivo and Recruits Nua4 To Promotmentioning
confidence: 99%
“…These transcription factors include (among others) Efg1p/ Flo8p, acting downstream of cAMP-PKA [14][15][16][17][18][19][20], Tec1p [21] and Ume6p [22,23]. Hyphal morphogenesis is also subject to negative regulation mostly by the general corepressor Tup1p through interaction with the transcriptional repressors Nrg1p and Rfg1p [4,12,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%